PENGARUH MODEL PEMBELAJARAN INKUIRI BERBASIS PROYEK TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK FASE E DI SMAN 1 PADANG - Fatira, Viona; Arsih, Fitri; Alberida, Heffi; Rahmatika, Helsa; Aulia Fikri, Refsya (Universitas Cokroaminoto Palopo, 2024)
Biology as part of science emphasizes learning that involves students directly through learning experiences that include science process skills. Based on the results of a preliminary study of the science process skills of phase E students at SMAN 1 Padang, it was obtained that the science process skills of students were still relatively low. This study aims to determine the effect of the project-based inquiry learning model on the science process skills of phase E students at SMAN 1 Padang. This type of research is a quasi-experimental study with a pretest-posttest control group design. The instrument used to measure students' science process skills is in the form of multiple choice questions. The sample class selected uses a purposive sampling technique. Data analysis using the paired sample test obtained significant results (0.000) <α value (0.05) so that it can be concluded that the project-based inquiry learning model has a positive effect on the science process skills of phase E students at SMAN 1 Padang.